Kitab himpunan perundang undangan negara Republik Indonesia: ditutup pada tanggal 3-8-1958 Jilid II - INDONESIA._[UNDANG_UNDANG_DAN_PERATURAN] (Kementrian Penerangan RI, 1958)
Oen, Jil.II=c.1-3/stoc6, jl.2=c.1-3